Musical Ability of Elementary School Studens: Rasch Model Analysis - Resa Respati; Rifqy Muhammad Hamzah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
Music education in Indonesian primary schools continues to face substantial challenges, primarily because most learning is delivered by classroom teachers who lack formal training in music education. This situation has resulted in a gap in the development of students’ musical abilities, despite the essential role of music in fostering cognitive, affective, social, and psychomotor growth. This study aims to analyze the musical abilities of primary school students taught by non-specialist classroom teachers. Employing a descriptive quantitative method, the research collected data through musical tests administered to 601 students from Tasikmalaya, Ciamis, Banjar, Garut, and Pangandaran districts/cities in West Java Province. The tests assessed three domains: rhythm imitation, melody imitation, and rhythm response. Instrument validity was examined using the Pearson Product Moment, while reliability was measured with Cronbach’s Alpha. Data were further analyzed using Rasch modeling through the Winstep application to obtain precise estimates of student ability and a detailed mapping of item distribution. The findings show that 13.98% of students demonstrated high musical ability, 70.55% moderate ability, and 15.47% low ability, with an overall mean ability of 0.72 logits. Rhythm response emerged as the most challenging domain compared with rhythm and melody imitation.